Chapter Intorno a Geografia Democratica. Fra Marx e Foucault, l'Italia e l''Ammerica' - Celata, Filippo (Territori, 2021)
Two main and sequential topics are emphasized. The first one is Quaini's attention for the historically and socially determinated building of the Man/Nature relation, which mainly characterizes his first works written against the remaining positivistic and deterministic interpretations of the so called '"Iintegral Ggeography"'. The other topic is the Hish/Low relation, metaphorically representing the dialectic among the social popular practices involved in the territorial exploitment and its representations, usually rooted into oral-tradition cultures, and, on the other side, those linked to the expert knowledges, irreplaceable to appropriately understand the space, always actually influenced by political powers and public institutions.